ANALISIS MAKNA KEMATIAN BAGI MASYARAKAT TORAJA DALAM CERPEN TUBUH TARRA, DALAM RAHIM POHON - Rakhmayanti, Fully Rakhmayanti; Pritanova, Nola; Damayantie, Augustia Rahma (Universitas Tanjungpura, 2024)
Short stories as a reflection of life, present various realities of life and culture that are inherent in humans. Toraja culture, which is depicted through a short story entitled in Di Tubuh Tarra, dalam Rahim Pohon, certainly carries its own meaning and views on death. Considering that each culture has its own beliefs in the meaning of death, this needs to be understood as a unique and distinctive cultural wealth of the archipelago. Through a qualitative approach, with heuristic and hermeneutic reading, analysis to interpret death in this short story is the focus of the research. This semiotic theory is used to reveal and complete the reading of meanings based on diction or language symbols that appear in the context of the story content. The results of meaning that can be traced through short stories include: 1) Death is a journey to puya (heaven); 2) burial places such as Passiliran and cave walls have meaning and rules for their use, 3) everybody that dies and is still in Tongkonan is considered to be still alive and sick and therefore needs care; 4) on the journey to the puya, every human being needs provisions and burial ceremonies or rituals that have been regulated by Toraja custom, Rambu Solo. By revealing this meaning, it can be concluded that the Toraja people have unique beliefs and views regarding death according to the customs they believe in.